Sulfide oxidation tuning in 4, 8-bis(5-(2-ethylhexyl)thiophen-2-yl)benzo[1, 2-b:4, 5-b′]dithiophene based dual acceptor copolymers for highly efficient photocatalytic hydrogen evolution. Issue 12 (21st February 2022) - Lin, Wei-Cheng; Jayakumar, Jayachandran; Chang, Chih-Li; Ting, Li-Yu; Huang, Tse-Fu; Elsayed, Mohamed Hammad; Elewa, Ahmed M.; Lin, Yu-Tung; Liu, Jia-Jen; Tseng, Yuan-Ting; Chou, Ho-Hsiu
Abstract : A sulfide oxidation tuning approach in BDTT is reported for constructing a series of dual acceptor1-2 (A1 –A2 )-type copolymers. PBDTTS-1SO achieved an outstanding HER, demonstrating that the immense potential of the A1 -A2 -type polymer photocatalysts. Abstract : Polymeric photocatalysts for hydrogen evolution by water splitting have drawn tremendous research interest in recent years. However, the relatively low photocatalytic hydrogen evolution efficiency still needs to be overcome for further development. Recently, a growing body of literature has shown that the sulfone group can act as an electron-output site owing to its strong electron-withdrawing ability. Therefore, this study reports a sulfide oxidation tuning approach in 4, 8-bis(5-(2-ethylhexyl)thiophen-2-yl)benzo[1, 2- b :4, 5- b ′]dithiophene (BDTT) for constructing a series of sulfone-based dual acceptor1-2 (A1 –A2 )-type copolymers with different numbers of sulfonyl groups and demonstrates that the A1 –A2 -type copolymer possesses the potential to supersede the D–A-type copolymer and A–A-type homopolymer. Moreover, the resulting polymer, PBDTTS-1SO displayed high photocatalytic activities of 97.1 mmol h −1 g −1 and 473 μmol h −1 (6 mg) under visible-light illumination and an apparent quantum yield exceeding 18% at a wavelength of 500 nm, which seems to be the highest value recorded among the reported polymer photocatalysts to date. This study presents an alternative material design strategy to boost photocatalytic efficiency.